Applause [videorecording (DVD)] - Zandvliet, Martin Pieter, 1971-; Steen, Paprika, 1964-; Falch, Michael; Maltha, Sara-Marie, 1971- ([publisher not identified], 2013)
Critically acclaimed alcoholic actress Thea Barfoed has gone through turmoil, resulting in a divorce and the loss of custody of her two boys. Eager to break with the past, regain control over her life, and get her children back, she uses charm and manipulation to persuade her ex-husband, Christian, that she is able to take back the mantle of motherhood. But ironically, she has not completely convinced herself.